Analisis Komparatif Kinerja Keuangan Empat Bank Terbesar di Indonesia Periode 2008 s/d. 2013 - Sahulata, Yulius YB (Universitas Sam Ratulangi)
The results of the study with one way ANOVA analysis showed: there is no significant difference between the financial performance of PT. Bank Mandiri (Persero) Tbk. PT. BRI(Persero) Tbk. PT. Bank Central Asia (Persero) Tbk. and PT. BNI (Persero) Tbk. (Hypothesis 1). Similarly, analysis of different test independent samples between each Bank found that there were no significant differences between the financial performance: PT. Bank Mandiri (Persero) Tbk. and PT. BRI (Persero) Tbk.Â Hypothesis 2), between PT. Bank Mandiri (Persero) Tbk. and PT. BCA (Persero) Tbk. (Hypothesis 3) between PT. Bank Mandiri(Persero) Tbk. and PT. BNI (Persero) Tbk. (Hypothesis 4) between PT. BRI (Persero) Tbk. and PT. BCA (Persero) Tbk. (Hypothesis 5) and between PT. BRI (Persero) Tbk. and PT. BNI(Persero) Tbk. (Hypothesis 7).. Keywords: financial performance